Obstetric emergencies and adverse maternal-perinatal outcomes in Ethiopia; A systematic review and meta-analysis - Leta, Masresha; Assefa, Nega; Tefera, Maleda (Frontiers in Global Women's Health, 2022)
Background: Obstetrical emergencies are life-threatening medical problems that develop during pregnancy, labor, or delivery. There are a number of pregnancy-related illnesses and disorders that can endanger both the mother and the child's health. During active labor and after delivery, Purpose: to assess the magnitude and association of obstetric emergency and adverse maternal-perinatal outcome in Ethiopia Method: We used four databases to locate article, PUBMED, HINARI , SCIENCE DIRECT and Google Scholar. Onwards, a search of the reference lists of the identified studies was done to retrieve additional articles. For this review, the PEO (Population, Exposure, and Outcomes) search strategy was used. Population: women who had Obstetrics Emergency in Ethiopia. Exposure: predictors of Obstetrics emergency, Outcome: adverse maternal & perinatal outcome. Ethiopian women was the outcome of interest. Synthesis of individual studies was conducted using Comprehensive meta analysis Software and STATA version 16.The presence of statistical heterogeneity was checked using the Cochran Q test, and its level was quantified using the I2 statistics. Summary statistic/s (pooled effect sizes) in odd ratio with 95% confidence intervals were calculated. Result: A total of thirty five studies were used for determining the pooled prevalence of adverse maternal & perinatal outcomes ,from them twenty seven were included to determine odd with 95% CI in the meta analysis and 40,139 women's who had obstetrics emergency. The magnitude of adverse maternal and perinatal outcome following obstetrics emergency in Ethiopia was 15.9% and 37.1% respectively as well as the adverse maternal outcome was increased by 95% in a mother having obstetrics emergency (OR 2.29 ,95% CI 2.43-3.52) and perinatal death also increase by 95% in a mother having obstetrics emergency (OR 3.84 ,95% CI 3.03-4.65) as compared with normo-tensive women. Conclusion: This review demonstrated the high prevalence of perinatal mortality among pregnant women with one of the obstetrics emergency in Ethiopia. Adverse maternal and perinatal outcomes following obstetrics emergency such as ICU admission, development of PPH , give birth via CS , maternal death , NICU admission , LBW and perinatal death were commonly reported in this study